The Semantic and Etymological Peculiarities of the Verbs of Blame - M. Timoshilova, Tamara M. Timoshilova; N. Morozova, Elena; V. Shemaeva, Elena; B. Kudryavtseva, Natalya; V. Golubeva, Julia (International Journal of Criminology and Sociology, 2022)
The article deals with the semantic analysis of the verbs of blame (brawl, castigate, condemn, curse, damn, lecture, rate, rebuke, reprehend, reprimand, reproach, reprobate, reprove, row, strafe, swear, trounce) in the perspective of semantics, as well as etymology. In accordance with the dominant cross-disciplinary approach to the linguistic research, the semantics of the verbs under study is analyzed in correlation with the relevant extra-linguistic data. It reveals the necessity of using some data of cognitive linguistics together with etymological methods of semantic analysis. The complex of cognitive and etymological methods helps to determine the functioning of the verbs in different kinds of discourse, and to find the closest equivalent in the Russian language.